2018
DOI: 10.21037/jtd.2017.12.65
|View full text |Cite
|
Sign up to set email alerts
|

High blood neutrophil-lymphocyte ratio associated with poor outcomes in miliary tuberculosis

Abstract: Pre-treatment NLR at admission may be a useful biomarker for mortality and development of ARDS in patients with miliary TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 29 publications
2
47
1
Order By: Relevance
“…NLR can be used as a prognostic marker in multiple diseases 12 14 , 17 19 , 22 , 23 . The value of NLR ranges from 0.78 to 3.53 in the healthy adult population 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NLR can be used as a prognostic marker in multiple diseases 12 14 , 17 19 , 22 , 23 . The value of NLR ranges from 0.78 to 3.53 in the healthy adult population 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The value of NLR ranges from 0.78 to 3.53 in the healthy adult population 21 . Although there is controversy on the optimal NLR cut-off values, numerous studies have reported that the NLR cut-off value for mortality in specific diseases is between 3 and 5 17 , 23 25 . The cut-off value of NLR for disease severity and activity in inflammatory bowel disease (IBD) is slightly lower compared with other medical conditions, ranging from 2 to 3 26 – 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, NLR has previously been associated with the subsequent development of TB disease (15) and the presence of active TB disease (including both pulmonary and extrapulmonary sites) (18)(19)(20)(21)(22)25), as well as the need for TB retreatment in previously-treated individuals (16), and development of acute respiratory distress syndrome (ARDS) in subjects with miliary tuberculosis (17). Most prior studies have reported that concurrent NLR is elevated in TB disease subjects relative to controls, but that NLR may be even further elevated in the setting of other acute respiratory infections (24).…”
Section: Discussionmentioning
confidence: 98%
“…A number of prior studies have evaluated CBC-derived ratios (MLR, NLR, and/or PLR) in the context of symptomatic TB disease, speci cally related to either predicting subsequent TB disease development, diagnosing TB disease, or monitoring disease response to antimicrobial therapy (5)(6)(7)(8)(9)(10)(11)(12)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). These studies were heterogeneous with respect to the geographic region from which participants originated, presence of comorbidities (such as HIV), age, concurrent use of TB therapy, and choice of control groups, making comparisons challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation